Lembaga istinbath di Indonesia - Maulidya, Baiq fina Fadhila (Maliki Interdisciplinary Journal, 2026)
The development of modern society has generated various religious and legal issues that are not always explicitly addressed in the primary sources of Islamic law. This situation necessitates a systematic and contextual process of istinbāṭ al-aḥkām to ensure the continued relevance of Islamic law in contemporary life. This article aims to examine the concept of istinbath in Islamic jurisprudence, its theoretical foundations and methodologies, as well as the role of istinbath institutions in the tradition and practice of Islamic law in Indonesia. This study employs a qualitative descriptive approach through library research, drawing on both classical and contemporary works in uṣūl al-fiqh and Islamic legal studies. The findings indicate that istinbath is an essential component of ijtihad, focusing on deriving legal rulings from textual sources using primary and secondary legal methods. In Indonesia, institutions such as the Indonesian Council of Ulama (MUI), Bahtsul Masail of Nahdlatul Ulama, and the Tarjih and Tajdid Council of Muhammadiyah play a strategic role in conducting collective ijtihad through diverse methodological approaches. These methodological differences reflect the dynamic nature of Islamic legal thought while also posing challenges in harmonizing fatwas within a plural society. Nevertheless, the presence of istinbath institutions in Indonesia significantly contributes to addressing contemporary religious issues in a responsive, authoritative, and maslahah-oriented manner.